2015
DOI: 10.1177/0363546515612082
|View full text |Cite
|
Sign up to set email alerts
|

Motivations Associated With Nondisclosure of Self-Reported Concussions in Former Collegiate Athletes

Abstract: Background Previous studies examining non-disclosure among athletes in various settings have found substantial proportions of athletes with undisclosed concussions. Substantial gaps exist in our understanding of the factors influencing athletes’ disclosure of sports-related concussions. Hypothesis/Purpose This cross-sectional study examined prevalence of, and factors associated with, non-disclosure of recalled concussions in former collegiate athletes. Study Design Cross-sectional survey. Methods Former … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
182
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 227 publications
(204 citation statements)
references
References 27 publications
16
182
6
Order By: Relevance
“…Because we did not ask students if they would report their concussion, but rather, would they continue to play, it is difficult to directly compare our findings to previous research. Generally speaking however, our observations appear to support the recent findings of Kerr et al (2016) who found, in males compared to females, a higher prevalence of not reporting concussions, and therefore continue to play with a concussion.…”
Section: Gender Attitude Differencessupporting
confidence: 89%
See 3 more Smart Citations
“…Because we did not ask students if they would report their concussion, but rather, would they continue to play, it is difficult to directly compare our findings to previous research. Generally speaking however, our observations appear to support the recent findings of Kerr et al (2016) who found, in males compared to females, a higher prevalence of not reporting concussions, and therefore continue to play with a concussion.…”
Section: Gender Attitude Differencessupporting
confidence: 89%
“…Similarly, Llewellyn, Burdette, Joyner, and Buckley (2014) reported no differences between gender in reporting of concussion symptoms. However, a more recent study, also using college athletes (Kerr et al, 2016), found the prevalence of not reporting concussions to be higher among men than women.…”
Section: Influence Of Gender On Continuing To Play And/or Not Reportmentioning
confidence: 93%
See 2 more Smart Citations
“…Second, we examined 27 sports, many of which, such as crew and golf, had not been previously examined. Furthermore, concussion disclosure may vary by sex and sport 29,30 and thus may further affect reported rates. Last, concussion incidence and reporting may be associated with additional environmental factors.…”
Section: Discussionmentioning
confidence: 99%